Parent-child relationship quality predicts higher subjective well-being in adulthood across a diverse group of countries - Jonathan T. Rothwell; Telli Davoodi (Communications Psychology)
Abstract Theoretically and empirically, parenting is closely related to the psychological health of offspring, but long-term effects and possible international differences are not well established. In a pre-registered multilevel modeling analysis using data from the Global Flourishing Study, we tested whether retrospective parent-child relationship quality predicts adult well-being in a representative sample of 202,898 adults living in 21 countries and one territory. We developed and validated indexes of flourishing and mental health. Retrospective parent-child relationship quality predicted both with substantial effect sizes for flourishing (std mean effect = 0.21, 95% CI 0.19–0.23) and mental health (std mean effect = 0.18, 95% CI 0.17–0.20). A positive association between relationship quality and flourishing was found in all 22 areas (significant in 21). Parental religiosity positively predicted relationship quality (std mean effect = 0.09, 95% CI 0.06–0.11). In higher income and more secular countries, relationship quality was lower, but the well-being benefits were higher. Parental religiosity predicted higher relationship quality in every country in the sample.